1998
DOI: 10.1111/j.2042-7158.1998.tb03338.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Absorption of Calcium after Oral Administration of Maltitol in the Rat Intestine

Abstract: The enhancing effects of maltitol (alpha-D-glucopyranosyl-1,4-sorbitol) on absorption of calcium by the rat intestine have been studied by use of [45Ca]CaCl2 in-vivo. After intragastric administration of [45Ca]CaCl2 solution with maltitol, plasma 45Ca concentration remained at the maximum level for more than 80 min, whereas for animals given [45Ca]CaCl2 solution without maltitol, plasma 45Ca concentration declined sharply after the peak. Determination of 45Ca radioactivity remaining in the various segments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Intraluminal infusion of sorbitol increases Ca absorption in the small intestine of rats (18). Using a tracer technique with 45 Ca, maltitol was found to stimulate Ca absorption in rats (19). In in vitro experiments using everted sacs or isolated preparations, maltitol (20), and polydextrose (21) were also seen to stimulate Ca absorption in the small intestine of rats.…”
Section: Discussionmentioning
confidence: 95%
“…Intraluminal infusion of sorbitol increases Ca absorption in the small intestine of rats (18). Using a tracer technique with 45 Ca, maltitol was found to stimulate Ca absorption in rats (19). In in vitro experiments using everted sacs or isolated preparations, maltitol (20), and polydextrose (21) were also seen to stimulate Ca absorption in the small intestine of rats.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, dietary lactose induced stimulation of Mg absorption in rats, and this was caused by a lowering effect on ileal pH [ 121 ]. Using a tracer technique with 45 Ca, maltitol was found to stimulate Ca absorption in rats, and osmotic activity of maltitol in small intestine was suggested to contribute to the increase in Ca absorption [ 122 ]. Other iS such as melibiose, DFA III, or DFA IV increased the permeability of intercellular passage, affected the epithelial tissue and opened the tight junctions of jejunum, ileum, cecum, and colon of rats [ 123 ].…”
Section: Effects On Nutrient Digestion Absorption and Systemic Mmentioning
confidence: 99%
“…Tsukamura et al (1998) reported that dietary maltitol (10 g/kg bw) has a protective effect against dimethylhydrazine-induced tumours in rat cecum and the proximal colon. Maltitol did not cause dental plaque (Maguire et al, 2000), and it increased the calcium absorption in the lower small intestine and increased the breaking force of femoral bones (Fukahori et al, 1998; Goda et al, 1998; Kishi et al, 1996). On the other hand, 40 g maltitol caused mild borborygmi, flatus and colic in healthy volunteers (Koutsou et al, 1996; Storey et al, 1998).…”
Section: Discussionmentioning
confidence: 99%